2022
DOI: 10.3389/fpubh.2022.1000840
|View full text |Cite
|
Sign up to set email alerts
|

Low-level EMF effects on wildlife and plants: What research tells us about an ecosystem approach

Abstract: There is enough evidence to indicate we may be damaging non-human species at ecosystem and biosphere levels across all taxa from rising background levels of anthropogenic non-ionizing electromagnetic fields (EMF) from 0 Hz to 300 GHz. The focus of this Perspective paper is on the unique physiology of non-human species, their extraordinary sensitivity to both natural and anthropogenic EMF, and the likelihood that artificial EMF in the static, extremely low frequency (ELF) and radiofrequency (RF) ranges of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 109 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Most international exposure guidelines for humans are based on acute short-term high-intensity exposures that are capable of heating tissue in a 6 ft. (1.8 m) adult male. However, the research database, as shown in Levitt et al ( 3 6 ) and Lai ( 7 ), verifies effects far below the current guidelines (see Discussion for further information on what human guidelines are based on). Radio-tagging is used today in species that range from ants to leviathans, not a 6 ft. (1.8 m) human model, and radio-tagging devices can entail a 24/7 exposure, depending on equipment and research project needs.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Most international exposure guidelines for humans are based on acute short-term high-intensity exposures that are capable of heating tissue in a 6 ft. (1.8 m) adult male. However, the research database, as shown in Levitt et al ( 3 6 ) and Lai ( 7 ), verifies effects far below the current guidelines (see Discussion for further information on what human guidelines are based on). Radio-tagging is used today in species that range from ants to leviathans, not a 6 ft. (1.8 m) human model, and radio-tagging devices can entail a 24/7 exposure, depending on equipment and research project needs.…”
Section: Introductionmentioning
confidence: 66%
“…While, to date, no radiation standards for nonhuman species have been developed, let alone implemented, by the U.S. Federal Communications Commission, the U.S. Environmental Protection Agency, or any international standards setting entity, the concerns continue to escalate, especially as the world’s wildlife continues to decline due to the ongoing sixth massive global species extinction event—the so-called Anthropocene (“Age of Man”) ( 97 – 99 ). What role EMF is playing as a part of this loss of species is of great potential concern, given nonhuman species’ unique physiology that evolved over millennia in a sensitive harmony/relationship with the Earth’s natural geomagnetic fields ( 3 6 ) upon which they depend for all life’s activities, and the fact that this is the fastest rising environmental exposure today. It is logical to assume that artificial EMFs are capable of affecting species with distinctive magnetoreception mechanisms and physiologies far more sensitive than humans, given the unusual signaling characteristics, odd wave forms, phased pulsing patterns, concentration of nonionizing radiation frequencies at the Earth’s surface and in lower atmospheric regions for the first time in evolutionary history, and at transmission intensities unlike anything in nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of anthropogenic electromagnetic fields on animals has been studied for quite a long time, and both beneficial and adverse effects on animals, depending on the frequency, intensity, and duration of exposure, as well as the specific characteristics of the animal and its environment, have been observed ( Levitt et al, 2022 ). The first reports on the magnetosensitivity of plants appeared almost a century ago ( Ssawostin, 1930 ).…”
Section: Introductionmentioning
confidence: 99%